The European significant risk transfer securitisation market - Fernando González; Cristina Morar Triandafil (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2023)
The European significant risk transfer (SRT) securitisation market is increasingly being used by major EU banks to manage risk and capital, but is not well known. SRT can provide an extra source of capital, flexibly and at a reasonable cost. Despite the bespoke nature of transactions, the SRT market has expanded significantly in the recent past to the point where it has now become a dependable way for banks to release capital, manage their balance sheets and improve their capital ratios. Banking supervisors assess SRT transactions to evaluate the degree of risk transfer from banks to investors, allowing institutions to achieve capital relief when this is considered sufficient. The market has become a permanent feature in European banks' capital management toolkit, alongside other standard but better-known instruments. Drawing on the ECB's unique and comprehensive database of SRT securitisations issued by large European banks supervised by the Single Supervisory Mechanism (SSM), we provide an overview of the main features of the European SRT market, a typology of the structures currently in use and an account of the market's evolution over the past five years. In so doing, we attempt to shed light on the main conceptual features of SRT securitisations in relation to non-SRT securitisation structures, as well as the regulatory processes behind capital relief that have been instrumental in supporting their increased use by European banks.
Keywords: G21; G28; G29; 330; Securitisations; significant risk transfer; capital requirements; guarantees; asset quality; lending conditions; government policy and regulation